Influence of Online Merging Offline Method on University Students’ Active Learning Through Learning Satisfaction - Yu, Huiju; Wang, Shaofeng; Li, Jiaping; Shi, Gaojun; Yang, Junfeng (Frontiers in Psychology, 2022)
Students’ active learning behavior determines learning performance. In post COVID-19 period, Online Merging Offline (OMO) method become a common way of university students’ learning. However, at present, there are few studies in active learning behavior in the OMO mode. Combined with learning satisfaction and Technology Acceptance Model (TAM), this paper proposes an Online Active Learning Model to predict the influencing factors of college students' active learning behavior and then analyzes the differences between OMO model and pure online model by multi group analysis (MGA) based on the model. The designed questionnaire was distributed and a total of 498 valid questionnaires were collected. Using SmartPLS to analyze partial least squares structural equation modeling (PLS-SEM) and MGA, it is found that: (1) there are differences in the influencing factors of active learning between OMO and pure online model; the moderating effect of learning complaint in OMO mode is not established, and social isolation and age does not affect active learning in OMO mode; 2) learning quality, perceived ease of use, expectation, perceived usefulness, and social isolation indirectly affect active learning through learning satisfaction in both OMO model and pure online model; 3) learning satisfaction is an important mediating variable affecting active learning; 4) learning complaints will negatively regulate the relationship between learning satisfaction and active learning only in pure online model. According to these findings, the paper provides theoretical and practical implementation suggestions implications for OMO teaching and online active learning to ensure the expected learning outcome.